Analysis of amino nitrogen content affecting fermentation and wine quality - Kállay, M.; Sárdy Nyitrainé, D. (International Journal of Horticultural Science, 2009)
A suitable amount of nitrogen source is needed for the optimal process of alcoholic fermentation. The professional literature mentions the complexity of nitrogen compounds exploitable for yeast-plants as an assimilable or immediately assumable nitrogen source. Former experiments proved that in case of low nitrogen concentration , yeast-plants produced a bigger quantity of hydrogen sulphide. According to the findings above, it is not indifferent when and how we complement the nitrogen content of the must. The aim of our present work was to elaborate such a quick, easily applicable method that can be used for routinish measurements in the viticultural practice.